Characterization of a New Transposon, Tn6696, on a blaNDM–1-Carrying Plasmid From Multidrug-Resistant Enterobacter cloacae ssp. dissolvens in China - Chen, Qichao; Lin, Yanfeng; Li, Zhonghong; Lu, Lanfen; Li, Peihan; Wang, Kaiying; Yang, Lang; Ma, Hui; Li, Peng; Song, Hongbin (Frontiers in Microbiology, 2020)
Abstract Background: Enterobacter cloacae (E. cloacae) is a pathogen which is responsible for serious nosocomial infections. A gene which plays an important role in resistance to carbapenems in E. cloacae is new Delhi metallo-β-lactamase 1 (NDM-1). Currently, the spread of E. cloacae which carry a plasmid containing blaNDM-1 is a serious public threat. Methods: A multidrug-resistant clone of E. cloacae, CBG15936, was recovered in 2017 in Guangzhou, China. PCR, S1-pulsed-ﬁeld gel electrophoresis, and Southern blotting were performed to identify and locate the blaNDM-1 gene. Susceptibility testing and conjugation experiments were also performed. Illumina HiSeq and Nanopore sequencers were used to perform whole genome sequencing. Results: Strain CBG15936 belongs to ST932 and is resistant to carbapenems. Correspondingly, a blaNDM-1 gene was found in the IncN1 plasmid of this strain. This plasmid is approximately ~62 kb in length and has a conjugation frequency of 1.68 × 10−3 events per donor cell. A new transposon, Tn6696, was also identified on this plasmid. Tn6696 consists of an intact qnrS1-carrying Tn6292 element, an inverted 8.3-kb Tn3000 remnant, ISkpn19, ΔtnpA, and IS26. Conclusion: A new transposon, Tn6696, has been detected on a blaNDM-1-carrying plasmid recovered from multidrug-resistant E. cloacae CBG15936 from China. This finding provides a new perspective regarding the potential for blaNDM-1 to undergo horizontal transfer among drug-resistant bacteria.